SÍFILIS MATERNA E CONGÊNITA NO BRASIL: ANÁLISE DOS PADRÕES ESPACIAIS, TEMPORAIS E ESPAÇO-TEMPORAIS - Chaiane Emilia Dalazen Botton (2023)
Syphilis in pregnant women (PW) is a public health problem, considering the risks of vertical transmission of congenital syphilis (CS) and unfavorables pregnancy outcomes such as prematurity, fetal and neonatal death. This study aimed to analyze the spatial, temporal and spatiotemporal dynamics of syphilis in pregnant women and congenital, in Brazil, from 2013 to 2019. It is an epidemiological study of the ecological and temporal series type and also descriptive of the reported cases of GS, CS and deaths from SC in children under one year of age in Brazil. Temporal trends in CS incidence and mortality and PW detection were examined using segmented linear regression. Univariate and bivariate global and local Moran indices and spatiotemporal statistics were used in the spatial and spatiotemporal analyses. Between 2013 and 2019, 317,779 cases of syphilis in pregnant women were reported in Brazil. The Southeast region concentrated 145,423 cases (45.8%), followed by the Northeast region with 66,188 (20.8%). There was an increasing trend in the detection rates of PW among pregnant women aged 20-29 years (AAPC: 0.8%; 95%CI: 0.4 to 1.1%), with more than 8 years of schooling (AAPC: 6.6%; 95%CI 5.2 to 8.0%) and with adequate treatment (AAPC: 15.4%; 95%CI: 8.2 to 19.1%). Municipalities with higher rates of syphilis in pregnant women had lower Social Vulnerability indices (Rho= -0.096; p<0.001) and an autocorrelation was identified between social vulnerability and syphilis detection rates in pregnant women (I= -0.10; p=0.001) and between estimated population coverage in PHC and PW rates (I= -0.092; p=0.001). The spatiotemporal cluster (RR= 2.04; p<0.001) of PW cases included 111,530 cases and involved the Southeast, Midwest and South regions. A total of 183,171 cases and 2,401 deaths from CS were registered in Brazil, with the highest number of cases in the Southeast region (n=82,612; 45.1%). There was an Increasing trend in CS rates among mothers aged 20-29 years (AAPC: 1.4; 95%CI: 1.0 to 1.7%) and with <8 years of education (AAPC: 6.6; 95% CI: 5.3 to 7.9%). The primary spatiotemporal cluster involved 338 municipalities in the Southeast region (RR=3.06; p<0.001). Autocorrelation was identified between social vulnerability and congenital syphilis incidence rates (I= 0.054; p= 0.001) and autocorrelation between estimated population coverage in PHC and congenital syphilis incidence rates (I= -0.123; p) = 0.001). To reduce trends in syphilis rates, it is necessary to develop actions aimed at groups with increasing trends (mothers aged 20-29 years) and at higher risk regions (Southeast, North and Northeast). The results provided important elements for future research and public health interventions, highlighting important regional differences.